BaeSR activates type VI secretion system expression in porcine extra-intestinal pathogenic Escherichia coli to enhance bacterial resistance to zinc stress. (October 2020) - Hu, Linlin; Wang, Chenchen; Lu, Wenjia; Lu, Hao; Chen, Huanchun; Tan, Chen
Abstract: The two-component system BaeSR is an extra-cytoplasmic stress response system in Escherichia coli, whose function is to be adapted to environmental stress. Recently, we have identified an active type VI secretion system in porcine extra-intestinal pathogenic Escherichia coli PCN033. DNA-protein interactions shows that BaeR directly binds to the promoter region of the T6SS and then induces its expression. Deletion of baeR/baeSR decreased zinc resistance of bacteria. Moreover, T6SS mutant Δhcp1/hcp2/hcp3 is more sensitive than wild type after exposure to external zinc, and complementation of hcp1 largely restored growth defect. Our study uncovers a new regulation mechanism of BaeSR system in response to metal stress. It reveals that BaeR-regulated T6SS is critical for bacteria survival under toxic zinc condition. In conclusion, T6SS contributes to zinc stress resistance in a BaeSR system-dependent manner. Highlights: A new regulator BaeR directly binds to the promoter of T6SS in ExPEC and regulate its expression. Response regulator BaeR is involved in the regulation of zinc homeostasis and bacterial zinc tolerance. We broaden the important physiological functions of T6SS in maintaining metal homeostasis in bacteria under stress.